2015
DOI: 10.1007/s00240-015-0762-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictive parameters for medical expulsive therapy in ureteral stones: a critical evaluation

Abstract: To evaluate the predictive value of some certain radiological as well as stone-related parameters for medical expulsive therapy (MET) success with an alpha blocker in ureteral stones. A total 129 patients receiving MET for 5 to 10 mm ureteral stones were evaluated. Patients were divided into two subgroups where MET was successful in 64 cases (49.61%) and unsuccessful in 65 cases (50.39%). Prior to management, stone size, location, position in the ureter, degree of hydronephrosis, diameter of ureteral lumen pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 18 publications
1
22
0
1
Order By: Relevance
“…The final report of the study was that HU is not a predictive parameter for stone expulsion [19]. In another study showing that stone size and localization, hydronephrosis grade, proximal ureteral diameter and ureteral wall thickness were highly associated with MET success rates, stone density was not shown to be associated with MET success [20]. However in this study, we determined that stone related factors on NCCT images such as stone diameter, volume and HU predicted stone expulsion rate at the end of 6 weeks of silodosin treatment for distal, mid and proximal ureteral stones with univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The final report of the study was that HU is not a predictive parameter for stone expulsion [19]. In another study showing that stone size and localization, hydronephrosis grade, proximal ureteral diameter and ureteral wall thickness were highly associated with MET success rates, stone density was not shown to be associated with MET success [20]. However in this study, we determined that stone related factors on NCCT images such as stone diameter, volume and HU predicted stone expulsion rate at the end of 6 weeks of silodosin treatment for distal, mid and proximal ureteral stones with univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that stone size and location are important parameters for predicting MET-success. 31 The definitive management of stones in these patients is usually deferred because approximately 68%-98% of stones <5 mm are expected to pass spontaneously. 32,33 As stone size increases, however, spontaneous passage becomes less likely; 34,35 the estimated spontaneous passage rate is 47% for stones >5 mm and <10 mm.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, ureteral stone(s) staying in the same position for a long period of time will impact into the ureteral wall (embed itself into the ureteric wall) due to inflammatory reaction-induced tissue changes in this part of the ureter. Additionally, the possible effect of UWT at the site of the stone as a predictive factor for final stone expulsion rates after MET has been evaluated in a recently published study, and UWT has been found to be a reliable predictor parameter [42] . Moreover, in their original study, Sarica et al [43] were able to show the predictive value of UWT on the SFR as well as additional procedure rates after SWL in ureteric stones with a cutoff value 3.55 mm over which additional procedure rates were found to be meaningfully high.…”
Section: Discussionmentioning
confidence: 99%